Sulodexide as pharmacotherapy for protection of endothelium and suppression of thrombosis in COVID-19 - A. M. Melkumyants; L. I. Buryachkovskaya; N. V. Lomakin; O. A. Antonova; V. V. Ermiskin; Y. V. Dotsenko («REMEDIUM GROUP» Ltd., 2022)
The article presents an overview of publications describing the mechanisms of the development of the pathological process in patients infected with SARS-CoV-2 coronavirus. The authors analysed publications showing that damage to the endothelium and endothelial glycocalyx is the main factor influencing the development of coronavirus COVID-19 infection. It is the endothelium inflammation caused by a virus that leads to the dysfunction of the vascular system and the development of coagulopathy. Using scanning electron microscopy and flow cytofluorimetry, we showed that patients with COVID-19 of moderate severity (CT2) had significant desquamation of endothelial cells (concentration of circulating endothelial cells (CEC) in blood is 300-400 cells/ml whereas the normal range is no more than 10 cells/ ml). Such desquamation should cause exposure of the pro-inflammatory and thrombogenic subendothelial matrix, which, as a results, leads to the development of thrombotic disorders of the circulatory system. Therefore, it is only natural to try to counteract disease progression by protecting the endothelial glycocalyx from damage. Sulodexide, a mixture of fast-moving heparin fraction (80%) and the glycocalyx element dermatan sulfate (20%) obtained from the mucous membrane of the small intestine of pigs, is very promising in this regard. This drug can significantly reduce the inflammatory process, protect the glycocalyx and endothelium from damage, resulting in lowering the degree of thrombus formation in patients with coronavirus COVID-19 infection, which relieves the course of the disease and improves its outcome. The experimental data presented in the review, although obtained in not large enough population of patients, allow us to consider sulodexide a promising drug that protects the endothelium and suppresses thrombosis in COVID-19.